Feasibility Assessment Model for Tourism Village: Evidence from Lebak, Indonesia - Arini Shofi Elmia; Syifaa Novianti (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
This study aims to evaluate the feasibility of developing a prominent tourism village in the Lebak Regency area. Due to limited resources, it is necessary to prioritize which villages have potential for successful development. Currently, there is a lack of standardized criteria for identifying tourist villages, posing challenges to their development. To address this issue, a combination of quantitative and qualitative approaches was employed in this research utilizing both primary and secondary data sources. The quantitative analysis involved scoring indicators formulated with nominal data types. Meanwhile, the qualitative analysis delved into understanding the meaning behind these scores. To integrate these two approaches, the quantitative scores were first used to identify patterns and flag high-potential villages resources, after which qualitative insights were applied to validate, refine, and contextualize the ranking results. This mixed-methods integration allowed the research to balance numerical prioritization with an understanding of local cultural, social, and environmental dynamics, ensuring a more holistic evaluation. Based on our findings, we determined that the Citorek Customary Wewengkon Area and Hegarmanah Village emerged as top contenders meeting all criteria required for designation as notable tourist destinations within Lebak Regency. Taking into account these results from our comprehensive analysis, it would be appropriate to consider prioritizing investment and further development efforts towards establishing Citorek Customary Wewengkon Area and Hegarmanah Village as key tourist attractions in Lebak Regency. This study has limitations regarding the scope of the selected research sites and indicator specificity which need to be improved.